Wellbeing for All: The Role of the Electoral System (The Macau Ricci Institute Journal, 2023)
Wellbeing for all is the result of effective politics. However, in most countries, the political environment is dominated by ethnic, religious, and economic cleavages, which drive politicians to cater to a fraction of the population rather than to society as a whole. Therefore, it is necessary to implement political institutions which encourage politicians to achieve wellbeing for all. But which institutions work? We suggest that much can be learned from Switzerland. While it has a highly diverse society, it is politically stable and economically wealthy. Traditionally, its success has been explained by federalism and direct democracy. We highlight the role of a third formal institution, the electoral system. Proportional and majority elections coexist at all levels of the Swiss state. In addition, the electoral system has specific features: majority elections usually take place in multi-seat districts, and they are often at-large elections, meaning that there is only one large district covering the whole jurisdiction.